PATHOGENIC VARIANTS IN THE NPM1 GENE IN PATIENTS WITH ACUTE MYELOID LEUKEMIA IN AMAZONAS STATE, BRAZIL - TCD Santos; GSP Braz; EN Assunção; MOD Santos; VC Costa; WO Azevedo; LNM Passos; AM Tarragô; LPS Mourão; GAV Silva (Hematology, Transfusion and Cell Therapy)
Background: Acute Myeloid Leukemia (AML) is a heterogeneous disease with different clinical and molecular manifestations, annually a disease with rates important of mortality. The AML is characterized by present genetic alterations, including variations in the Nucleophosmin (NPM1) gene, occur in 30-45% of AML cases. These variants are considered significant biomarkers that classify and determine patient risk stratification and treatment. Objective: To evaluate the presence of pathogenic genetic variants in the coding region of the NPM1 in AML patients from the Hematology and Hemotherapy Foundation of the State of Amazonas (HEMOAM). Materials and methods: Bone marrow samples were collected of 18 AML patients. Were performed, RNA extraction, complementary DNA synthesis, conventional polymerase chain reaction (PCR), and genetic sequencing. Clinical, epidemiological, and laboratory data were analyzed from physical and electronic records of the HEMOAM, with statistical analyses performed to describe and determine the findings. Pathogenic variants were identified from the obtained sequences, also analyzed the Variant Allele Frequency (VAF) and classified according to CancerVar. Results: The study population present a higher prevalence of females, 11 (61%), an average age of 50 years (± 23.55). Regarding laboratory data, patients presented with erythropenia, thrombocytopenia, and leukocytosis, with counts of 2,637 × 10/mm3, 43,500/mm3, and 45,346/mm3, respectively. The classical variant (type-A), c.864_867dupTCTG (W288Cfs), was identified in 3 patients (16%), while the pathogenic c.385C>G (E129Q) variant in 18 (100%). Curiously, 11 patients (11/18) carrier the E129Q variant, and 3 (3/11) carrier both W288Cfs and E129Q variants, which led to death outcomes. Furthermore, these patients demonstrated a Variant Allele Frequency (VAF) exceeding 40%, with a mean VAF of 44% [41% - 61%] and 43% [40% - 47%], respectively. Discussion: In this study, a low frequency of the W288Cfs variant was observed, which differs from other studies. However, the VAF results are consistent with studies highlighting that patient with a burden exceeding 40% for the NPM1, indicate high allele load, may contribute to the onset of leukemogenesis. Furthermore, a high VAF may indicate resistance to chemotherapy treatment, influencing lower patient survival rates. Conclusion: Pathogenic variants and increased allelic load in the NPM1 were frequently observed in AML patients, possibly related to hematological alterations. Our study highlights the importance of variant analysis in the coding region of NPM1 through genetic sequencing, evaluation of mutational allelic burden quantification of NPM1 variants at diagnosis is essential to define the risk stratification profile and providing information for therapeutic approaches in disease treatment.